THE FUTURE OF MOBILE CLOUD COMPUTING: KEY IMPLICATIONS AND CHALLENGES - Nosheen, Ammber; Omar, Mohd Adan (TOPLAMA, 2024)
This research aims to examine the future development of Mobile Cloud Computing (MCC) and identify the key implications and challenges that this technology will face. In the face of the technological revolution, especially with the adoption of 5G networks and integration with the Internet of Things (IoT), MCC has the potential to transform various industry sectors. The study employs a qualitative methodology through a literature review and semi-structured interviews with experts in cloud technology, mobile computing, and technology policy. The literature review is conducted to understand the latest technological trends and the challenges faced by MCC, while interviews provide direct insights from industry practitioners and policymakers about the future of MCC. The research findings indicate that MCC will increasingly integrate with 5G technology and IoT, enabling the adoption of more complex applications such as augmented reality (AR), virtual reality (VR), and artificial intelligence (AI). However, several key challenges need to be addressed, such as data security issues, reliance on network infrastructure, and regulations that are not yet fully adaptive to MCC developments. Experts emphasize the importance of enhancing security standards, developing edge computing to reduce latency, and fostering collaboration between governments and industry to create policies that support innovation.